2011
DOI: 10.1111/j.1525-142x.2011.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Tail regression induced by elevated retinoic acid signaling in amphioxus larvae occurs by tissue remodeling, not cell death

Abstract: The vitamin A derived morphogen retinoic acid (RA) is known to function in the regulation of tissue proliferation and differentiation. Here, we show that exogenous RA applied to late larvae of the invertebrate chordate amphioxus can reverse some differentiated states. Although treatment with the RA antagonist BMS009 has no obvious effect on late larvae of amphioxus, administration of excess RA alters the morphology of the posterior end of the body. The anus closes over, and gut contents accumulate in the hindg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…Previous studies in the Florida amphioxus, B. floridae , have shown that the administration of excess RA during gastrulation results in a small anus [39] and that the continuous administration of RA to B. floridae larvae leads to closure of the anus and regression of the tail fin [51]. Our data on the European amphioxus, B. lanceolatum , are consistent with these previous findings and further suggest that RA signaling is required for proper tail fin outgrowth.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies in the Florida amphioxus, B. floridae , have shown that the administration of excess RA during gastrulation results in a small anus [39] and that the continuous administration of RA to B. floridae larvae leads to closure of the anus and regression of the tail fin [51]. Our data on the European amphioxus, B. lanceolatum , are consistent with these previous findings and further suggest that RA signaling is required for proper tail fin outgrowth.…”
Section: Discussionsupporting
confidence: 91%
“…This downregulation in turn is likely responsible for the induction of tail fin regression upon RA treatments in B. floridae larvae [51]. Our results of RA and CYP26 inhibitor treatments in B. lanceolatum are generally consistent with these previous observations, although we identified a major difference in the developmental timing of the involvement of RA signaling in tail fin outgrowth between the two amphioxus species.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations